Analisis Peran Pengembangan Desa Wisata Dalam Meningkatkan Kesejahteraan Masyarakat Dan Kaitannya Pada Pencapaian Sustainable Development Goals (Studi Kasus Desa Wisata Denai Lama Kecamatan Pantai Labu Kabupaten Deli Serdang) - Kiki Meisya Putri; Muhammad Arif; Sri Ramadhani (Universitas Labuhanbatu, 2022)
Poor people in Indonesia are more in rural areas than urban areas. In Denai lama village, the majority of the people are farmers and housewives or do not work. This tourist village was formed with the aim of helping the economy of the community. Desa wisata is one of the tourism sectors that is expected to realize the goals of the Sustainable Development Goals. This study aims to determine, first to determine the role of Tourism Village in improving the welfare of the community, second to determine the role of Tourism Village by linking it to the achievement of several points of Sustainable Development Goals, third to determine the constraints in the development of Tourism Village. The research approach in this research is descriptive qualitative with data collection method that is using observation, interview and documentation techniques. The results of the study concluded that first, the existence of a tourist village contributes greatly to the economy of the community, the income of the community increases and it can be said that with this tourist village the life of the community becomes prosperous. Second, the existence of tourism villages has a positive impact on several points of the Sustainable Development Goals, namely on the points of healthy and prosperous life, quality education, Gender equality, and Decent Work and economic growth, but in the points of poverty alleviation has not been fully resolved. The three obstacles that exist in the development of tourist villages are still a lot of infrastructure that must be built and in the process of development, also in giving a conscious understanding of tourism to the community is still an obstacle. And still have to create quality human resources.